A Thematic Analysis of Clients' Reflections on the Qualities of Group Work for Sex and Pornography Addiction. Issue 1 (2nd April 2020) - Hall, Paula; Larkin, Jo
Abstract: A sample group of 19 recovering sex and porn addicts who had attended both one-to-one and group therapy at the Laurel Centre sex addiction clinic in the UK undertook an hour-long semi-structured interview relating to the usefulness of group work to their recovery. Interview data was analysed for themes and cross-referenced with Yalom's 11 therapeutic factors of group therapy (Yalom and Leszcz, 2005 ). Some additional themes were also found that related specifically to the Hall Recovery Course psycho-educational programme that they each attended. Group work was found to be more important to participants' recovery than one-to-one therapy but this was not consistent, and drawbacks to group work were also identified.